Nerve fibres in isolated segments of dog ulnar nerves after complete brachial plexotomy and periaxilar artery sympathectomy - Eros Abrantes Erhart; Cecil J. Rezze (Arquivos de Neuro-Psiquiatria)
Experiments were performed in adult dogs in order to study our reported observation of normal nerve fibres in the intermediate and distal segments of nerves completely separated from the proximal stump for more than six months. The results obtained confirmed once more our previous observation: there are normal nerve fibres and nerve bundles repopulating the pattern fascicles of the completely separated intermediate and distal segments of the ulnar nerve, although all other nerves of the operated limb, including the proximal stump of the ulnar, show a typical Wallerian degeneration. It seems, therefore, that these fibres of normal appearance must have arisen from a source other than the proximal ulnar nerve stump, neighbour nerves or "Nervi-vasorum". More concrete data about these findings are naturally necessary and our experiments are going on. Even so, as stated before, the practical results obtained up to now in more than one hundred and fifty patients allows us to go on recommending strongly, based on our observations, that proper nerve suture or neurolisys of long-time severed nerves by accident are worth while even after delays of many years.